History of Chronic Traumatic Encephalopathy - Cantu, Robert C.; Bernick, Charles (Seminars in Neurology, 2020)
The long-term effects of repetitive head impacts have been recognized for close to a century. What is now referred to as chronic traumatic encephalopathy (CTE) was first described by Martland in 1928 in a series of boxers. Over the years, several important articles were published, including Critchley's 1957 report where he introduced the term “chronic traumatic encephalopathy,” Robert's study in 1969 which provided evidence of the prevalence of neurological impairment in retired fighters, and Corsellis' initial description of the pathology of CTE. However, what brought public attention to the issue of CTE in sports were the postmortem findings of CTE pathology in professional American football players, initially reported by Omalu and subsequently in a large series by McKee. There is now standardization of pathological criteria for CTE and recognition that it can be seen across all activities that involve repetitive head impacts.
Keywords: chronic traumatic encephalopathy; brain damage; natural history